Painting the Target Around the Arrow: Two-Step Prodrug Therapies from a Carbohydrate Chemist's Perspective - Houston, Todd A. (Current Drug Delivery, 2007)
Selective accumulation of an exogenous enzyme or activating agent at a target cell allows use of prodrugs that will be unmasked only at this site. This can reduce the side effects of chemotherapy and allow more potent drugs to be used in various treatments. Examples of this two-step prodrug therapy include antibody- (ADEPT, ADAPT), genetic- (GDEPT, VDEPT) and macromolecule-based approaches (PDEPT, LEAPT). Carbohydrate chemistry and glycobiology feature in each of these areas and is the focus of this review.
Keywords: prodrugs